The Notes on Mammal Carcasses Collected in Pangandaran Nature Reserve, West Java, Indonesia - Yamato Tsuji; Bambang Prayitno; Ona Norwana; Emiko Nishi; Kanthi Arum Widayati; Akichika Mikami; Bambang Suryobroto (HAYATI Journal of Biosciences, 2016)
A field survey was conducted in Pangandaran Nature Reserve (PNR), West Java, Indonesia between 2011 and 2015, during which fresh carcasses of wild mammals were collected. Body sizes of these carcasses were performed. This paper reports relevant data for future applications.